Synthesis of crown ethers bearing 2,4-dinitrophenylhydrazone - (:unkn) unknown (WILEY, 2007)
The o-dihydroxy- (2a-b), dimethoxy (3a-b), ethylendioxy- (4a-b) and macrocyclic polyethers (4c-i) are the initial compounds while the 2,4-dinitrophenylhydrazone compounds (5a-d, 6a-i) represent new derivatives. Novel hydrazone compounds were synthesized from the corresponding cyclic ketones (4a-i) and 2,4-dinitrophenylhydrazine in H2SO4/EtOH/H2O solution at room temperature for 1 h. The structures of obtained hydrazone compounds were confirmed by 'H-NMR, C-13-NMR, EI-MS, IR spectra and elemental analysis.
Keywords: COUMESTAN ANALOG DERIVATIVES; CONDUCTOMETRY; COMPLEXATION